Comparative morphology of the prothoracic leg in heliconian butterflies: Tracing size allometry, podite fusions and losses in ontogeny and phylogeny. Issue 4 (July 2017) - Moreira, Gilson R.P.; Silva, Denis S.; Gonçalves, Gislene L.
Abstract: Prothoracic legs of heliconian butterflies (Nymphalidae, Heliconiinae, Heliconiini) are reduced in size compared to mesothoracic and metathoracic legs. They have no apparent function in males, but are used by females for drumming on host plants, a behavior related to oviposition site selection. Here, taking into account all recognized lineages of heliconian butterflies, we described their tarsi using optical and scanning electron microscopy and searched for podite fusions and losses, and analyzed allometry at the static, ontogenetic and phylogenetic levels. Female tarsi were similar, club-shaped, showing from four to five tarsomeres, each bearing sensilla chaetica and trichodea. Male tarsi were cylindrical, formed from five (early diverging lineages) to one (descendant lineages) either partially or totally fused tarsomeres, all deprived of sensilla. Pretarsi were reduced in both sexes, in some species being either vestigial or absent. Tarsal lengths were smaller for males in almost all species. An abrupt decrease in size was detected for the prothoracic legs during molting to the last larval instar at both histological and morphometric levels. In both sexes, most allometric coefficients found at the population level for the prothoracic legs were negative compared to the mesothoracic leg and also to wings. Prothoracic tarsi decreased proportionally in size over evolutionary time; the largest and smallest values being found for nodes of the oldest and youngest lineages, respectively. Our results demonstrate that evolution of the prothoracic leg in heliconian butterflies has been based on losses and fusions of podites, in association with negative size allometry at static, ontogenetic and phylogenetic levels. These processes have been more pronounced in males. Our study provided further support to the hypothesis that evolution of these leg structures is driven by females, by changing their use from walking to drumming during oviposition site selection. In males the leg would have been selected against due to absence of function and thus progressively reduced in size, in association with podites fusions and lost. Highlights: Heliconian butterfly prothoracic tarsi are compared under optical and scanning electron microscopy. Corresponding allometry was analyzed at the static, ontogenetic and phylogenetic levels. Allometry, fusions and losses of podites were traced in the heliconian butterfly phylogeny. There were fusions and losses of podites, in association with negative size allometry at all levels. In both sexes, prothoracic tarsi decreased proportionally in size on evolutionary time.